Ecological perspective in creativity of the Kazakh publicists at the turn of XX – ХХІcenturies (Herald of Journalism, 2016)
In the article environmental problems which found the reflection in the Kazakh journalism are considered. The author investigates the materials of the press devoted to various environmental issues. From the moment of finding of independence by Kazakhstan and till today this subject doesn’t lose its urgency.
Keywords: censorship; colonization; publicist